Enhancing student engagement and active learning through student presentation-based effective teaching (SPET) method among Malaysian undergraduate students - Meganathan, Pavani Malaa (Infrastructure University Kuala Lumpur Malaysia, 2024)
This study investigates the impact of the Student Presentation-Based Effective Teaching (SPET) approach on Malaysian undergraduate students. Utilising a qualitative research design, the research aims to explore how student presentations influence classroom participation and the overall learning experience in higher education. A total of 46 participants, aged 20 to 23, enrolled in a Bachelor of Arts program, participated in this study over a 14-week semester at a public university in Malaysia. Data were collected through a combination of observation, field notes, student presentations, personal communications (such as WhatsApp messages), and teacher evaluations, employing convenience sampling for its efficiency and accessibility. The findings reveal that integrating presentations into the curriculum fosters critical thinking, enhances student motivation, and facilitates a more effective learning experience. Students expressed that preparing and delivering presentations not only improved their understanding of complex topics but also encouraged them to engage in collaborative learning activities. Post-presentation tasks, such as quizzes and interactive games, further enriched the learning environment, promoting both cognitive and physical engagement.